Schwann cells seeded in acellular nerve grafts improve functional recovery. Issue 2 (22nd November 2013) - Jesuraj, Nithya J.; Santosa, Katherine B.; Macewan, Matthew R.; Moore, Amy M.; Kasukurthi, Rahul; Ray, Wilson Z.; Flagg, Eric R.; Hunter, Daniel A.; Borschel, Gregory H.; Johnson, Philip J.; Mackinnon, Susan E.; Sakiyama‐Elbert, Shelly E.
ABSTRACT Introduction: This study evaluated whether Schwann cells (SCs) from different nerve sources transplanted into cold‐preserved acellular nerve grafts (CP‐ANGs) would improve functional regeneration compared with nerve isografts. Methods: SCs isolated and expanded from motor and sensory branches of rat femoral and sciatic nerves were seeded into 14mm CP‐ANGs. Growth factor expression, axonal regeneration, and functional recovery were evaluated in a 14‐mm rat sciatic injury model and compared with isografts. Results: At 14 days, motor or sensory‐derived SCs increased expression of growth factors in CP‐ANGs versus isografts. After 42 days, histomorphometric analysis found CP‐ANGs with SCs and isografts had similar numbers of regenerating nerve fibers. At 84 days, muscle force generation was similar for CP‐ANGs with SCs and isografts. SC source did not affect nerve fiber counts or muscle force generation. Conclusions: SCs transplanted into CP‐ANGs increase functional regeneration to isograft levels; however SC nerve source did not have an effect. Muscle Nerve49: 267–276, 2014